Determining the efficiency of selected vegetated biofilters in reducing nutrients from urban stormwater in the city of Ekurhuleni, South Africa - Bvumbi, Mulalo Justice (Vaal University of Technology, 2021)
Over time, the quality standard of stormwater in the City of Ekurhuleni (CoE) has deteriorated due to industrial, commercial, residential and farming activities. Stormwater quality directly impacts the treatment chain of potable water, and therefore, it should be kept in check at all stages. Innovations in the biofiltration process can provide useful, practical solutions to overcome crucial stormwater pollution problems. In 2013, the CoE developed stormwater design guidelines and standards to be implemented for the design of stormwater management, which include the principles of Water Sensitive Urban Design (WSUD) and Sustainable Urban Drainage Systems (SuDS) in particular. The CoE stormwater design guidelines and standards do not provide details on how the city plans to implement SuDS treatment trains to reduce stormwater pollution experienced by the city. This study aimed to verify the efficiency and effectiveness of vegetated biofilters on the stormwater treatment using CoE – Olifantsfontain's natural stormwater and to determine the most suitable vegetation to be used in the region. The CoE experimental case study was conducted to assess the efficiency of selected vegetated biofilters in lowering the concentration of orthophosphate (PO4-3), ammonium (NH4+), and nitrate (NO3-) from Tembisa/Olifantsfontain stormwater. In the experimental setup, six selected plant species were planted into 30 vegetated biofilter columns, namely: Agapanthus praecox (Dryland plant), Carpobrotus edulis (Dryland plant), Stenotaphrum secundatum (Dryland plant), Zantedeschia aethiopica (Wetland plant), Typha capensis (Wetland plant) and Phragmites australis (Wetland plant). The six species were grouped according to general habitats, i.e. three wetland and three dryland plants. Wetland plants were planted into fifteen vegetated biofilters, and dryland plants were also planted on another fifteen vegetated biofilters. The biofilters contained layers of sandy loam soil, coarse and and gravel sand. Each biofilter had a designated inlet and outlet section fitted with a gate valve to control retention time. The raw stormwater consisting of natural nutrient pollutants was applied to each vegetated biofilter through the inlet section. The samples were collected from the inlet and outlet of the six grouped vegetated biofilters during the month of June. All six plant species reduced outflow concentrations of PO4-3 and NH4+ by an average of 99% and 98%, respectively. The results also show that all plant species excluding Phragmites australis were able to reduce NO3- with outflow concentrations being reduced by an average of 58%. From the results obtained, it may be concluded that all the six plant species may be suitable variants to be applied as biofilter material for the purposes of treating urban stormwater in the CoE. The reason is that the determined removal efficiencies for bio-retention fall within 50% – 60% for PO4-3, and 40% - 50% for NH4+ and NO3- respectively. The results also show that if the plant species were applied for SuDs in the CoE, there could be a great improvement in the urban stormwater quality with the consequent improvement in both surface and groundwater quality of the receiving water bodies in the area. Regardless of the nutrient removal by selected plant species, the inclusion of vegetation in a field setting would slow flow rates and thus encourage infiltration into the soil, improve water quality, and support urban biodiversity. In the CoE, all the selected species could be used in the SuDS treatment trains targeting PO4-3, NH4+ and/or NO3-. The case study results provide a informed records for the CoE in the future/intended application SuDs in the upgrade/rehabilitation of its stormwater system.
M. Eng. (Department of Civil Engineering, Faculty of Engineering and Technology), Vaal University of Technology.
Keywords: Vegetated biofilters; Reducing nutrients; Stormwater biofiltration; Removing nutrients; Crucial stormwater pollution; Orthophosphate; Ammonium; Nitrate; Dissertations, Academic -- South Africa.; Water -- Purification -- Fixed-film biological process.; Stormwater infiltration.